Factors influencing lifelong learning at workplace: the experience of Thai and Malaysian human resource managers - Benjasom, Muhammad Husnee; Mhd. Sarif, Suhaimi (2012)
This paper investigates factors that influence lifelong learning experience at workplace of Thai and Malaysian companies. The informants of this study are human resource (HR) managers of Thai and Malaysian companies. The study used personal interview with Thai and Malaysian HR managers. Informants were asked to provide important factors for lifelong learning initiatives and the HR managers’roles for lifelong learning at their respective companies. The results showed key factors for lifelong learning at workplace include (a) business decisions that influenced by global and local events, (b) proper recognition and reward system, and (c) unique capability of managers to influence via managerial roles opportunities within the organizational culture’s values. However, the results of the study are not conclusive and cannot be generalized. The study proposes future studies to use case studies method and to include key business stakeholders into the focus group discussion.